A clinicopathogical study on diabetic foot ulcer with special reference to the causative factors and its management - Paul, Sailendranath; Das, Dilip Kumar (International Surgery Journal, 2019)
Background: Diabetic ulcers are the most common foot injuries leading to lower extremity amputation. The present study was done to identify the incidence and related risk factors of diabetic foot ulcers in study participants. Methods: This was a prospective done on 50 patients with diabetic foot ulcers. All the patients were examined thoroughly and related laboratory investigations were done. Wound culture and sensitivity was done in all cases. Results: Mean age of onset with foot ulcers was 53.5 yrs in male and 55 yrs in females. Nephropathy was present in 12 (24%) patients. Sensorimotor neuropathy was present in 29 (58%) cases and autonomic neuropathy was present in 06 (12%) cases. Most common infection identified in diabetic foot ulcers was due to gram-negative bacteria (E. coli in 45 cases). Major amputation was done in 2 (4%) patients. Conclusions: Implementation of management strategies at early stages prevents the development of complications related to diabetic foot ulcers in patients.